Brand Experience and Service Quality in Influencing Customer Engagement in Wardah Cosmetics Brand - Hafidh, Muhammad; Muthohar, Muchsin (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2023)
Cosmetic products are growing from time to time. In addition to the high demand, the development of products that use natural ingredients is a factor in the community's high demand for cosmetic products. However, there has recently been a decline in brand selection for cosmetic products, so it is essential to identify the predictors that result from it. This study aims to analyze the role of brand experience and service quality in influencing customer engagement with the Wardah Cosmetics brand. This study used a quantitative design. Data were collected by distributing online questionnaires to 220 randomly selected respondents domiciled in Java and surrounding areas. The questionnaires distributed met the validity and reliability tests through piloting previous studies. All collected data were analyzed using SmartPLS version 3.2.9 with a significance level of 95% (p<0,05). This finding obtained the productive age between 20 and 25 dominating among respondents domiciled in Yogyakarta. Confirmation of the hypothesis found that brand experience and love influence customer engagement directly and indirectly in significant direction. This indicates that this factor determines the younger generation's high interest in cosmetic surgery.